2020
DOI: 10.1080/14767058.2020.1818202
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus is associated with antenatal hypercoagulability and hyperfibrinolysis: a case control study of Chinese women

Abstract: Background: To determine the relationship between gestational diabetes mellitus (GDM) and coagulation/ brinolysis abnormality in antenatal Chinese women. Methods: Case control study. Fifty women had GDM and 132 did not (the NGDM group) grouping by the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria. Maternal plasma biochemistry and previous medical history were collected from perinatal health records. Antenatal coagulation/ brinolysis activity(CFA) parameters was assessed usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…[5,6] Studies have revealed increased circulating levels of the inflammatory markers, fibrinogen, C-reactive protein and leukocyte, in GDM women, thereby showing that the maternal inflammatory response is established during the earliest phases of implantation. [4,7,8] Platelets and erythrocytes, like leukocytes, also play an important role in the inflammatory response. Activated platelets can release considerable quantities of chemokines and express a multitude of immune receptors on their membranes that are involved with inflammation by binding to neutrophils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] Studies have revealed increased circulating levels of the inflammatory markers, fibrinogen, C-reactive protein and leukocyte, in GDM women, thereby showing that the maternal inflammatory response is established during the earliest phases of implantation. [4,7,8] Platelets and erythrocytes, like leukocytes, also play an important role in the inflammatory response. Activated platelets can release considerable quantities of chemokines and express a multitude of immune receptors on their membranes that are involved with inflammation by binding to neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…In women, GDM tends to present with an inflammatory response, which is likely to play a role in insulin resistance [5,6] . Studies have revealed increased circulating levels of the inflammatory markers, fibrinogen, C-reactive protein and leukocyte, in GDM women, thereby showing that the maternal inflammatory response is established during the earliest phases of implantation [4,7,8] …”
Section: Introductionmentioning
confidence: 99%
“…Our findings are contrary to findings by Liu et al, who demonstrated using TEG and conventional coagulation tests, that GDM is associated with hypercoagulability and hyperfibrinolysis in a case control study. Again, this study did not report on the level of glycaemic control in their GDM group 29 . However, women in the GDM group ( n = 50) were significantly older and heavier in weight than those without GDM ( n = 132) (30.3 vs 28.6 years; 61.8 vs 56.0 kg).…”
Section: Discussionmentioning
confidence: 74%
“…Again, this study did not report on the level of glycaemic control in their GDM group. 29 However, women in the GDM group (n = 50) were significantly older and heavier in weight than those without GDM (n = 132) (30.3 vs 28.6 years; 61.8 vs 56.0 kg). Both increased age 30,31 and BMI [16][17][18][19][20][21][22] are associated with increased hypercoagulability, and these factors could have contributed to the greater magnitude of hypercoagulability in the GDM group.…”
Section: Discussionmentioning
confidence: 90%
“…Endothelial damage caused by high blood glucose activates the internal coagulation system in pregnant women with GDM ( 21 , 22 ), and some studies have also shown that the level of coagulation factor XII in pregnant women with GDM was significantly higher than healthy pregnant women ( 23 ). The reason might be that endothelial damage caused by high blood glucose activates the internal coagulation system in pregnant women with GDM.…”
Section: Discussionmentioning
confidence: 99%